Analysis of Interleukin-8 and Interleukin-6 Levels Post Urinary Catheter Insertion in Pelvic Organ Prolapse Surgery - Ramadhani Anwar, Fadhilah; Ahmadi Farid, Imam; Nur Asni, St.; Irianta, Trika; D. Kouwagam, Anggrainy; Susiawaty, Susiawaty (Journal of Neonatal Surgery, 2025)
Background: Pelvic organ prolapse (POP) can cause pressure on the urethra, causing urinary problems and increasing the risk of urinary tract infection (UTI). Interleukin (IL)-8 and IL-6 are cytokines produced in response to bacterial infection but have been reported inconsistently in UTI. This study aims to analyze the relationship between urinary IL-8 and IL-6 levels with UTI before and after urinary catheter insertion in POP surgery. Methods: This study is an observational study in women who will undergo POP surgery at Wahidin Sudirohusodo Hospital and Network Hospital from March to October 2024. Urine samples of patients were taken before catheter insertion in POP surgery and during catheter removal after pelvic organ surgery. IL-8 and IL-6 levels were measured using ELISA kits. Statistical analysis used the Mann Whitney test and Kruskal Wallis test. Results: Total of 44 women were collected, most of whom were 50-70 years old, multiparous and obese. Urinary IL-8 and IL-6 levels were significantly different before and after urinary catheter insertion in patients undergoing POP surgery (p < 0.05). Changes in IL-8 levels after urinary catheter insertion were greater than changes in IL-6 levels after urinary catheter insertion (p < 0.05). IL-6 levels did not differ significantly based on age, parity and BMI (p > 0.05). Urinary IL-8 levels were significantly different based on age and parity (p < 0.05), not significantly different based on BMI (p > 0.05). Conclusion: Urinary IL-8 and IL-6 levels increased after urinary catheter insertion in POP surgery